تصميم منهج الدورة والتدريبات في اللغة العربية للمستوى التمهيدي في مركز الدورات والتدريبات بجامعة دار السلام كونتور - Muhammad Syamsul Arifin; Mohammad Syauqhi Radjfi; Mandrasi Amira Sa’idah (PPPBA, 2025)
This research was conducted to analyze the design of the Arabic language education and training curriculum at the pre A1 level based on the CEFR at the Center for Education and Training (Pusdiklat) UNIDA Gontor. The focus of this study is on the Arabic language training provided for intermediate-level participants who are very beginner to learning Arabic actively and communicatively. A qualitative approach and Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) were employed in this research. Practically, this study is currently at the second stage, 'design,' of the ADDIE model, following a needs analysis conducted with the training participants. Data were obtained through interviews and documents related to the Arabic language training that has been conducted by the Center for Education and Training UNIDA Gontor which was analyzed throughout content analysis. The research findings indicate that: 1) the majority of Arabic language training participants are intermediate-level students who are just beginning to learn Arabic in an active and communicative manner (introductory level); 2) the Center for Education and Training refers to the language proficiency levels established by the Directorate of Language Development (DLD) at UNIDA Gontor based on the CEFR with modifications; 3) the pre A1 proficiency level at the UNIDA Gontor Training Center allows participants to use Arabic vocabulary in simple and acceptable conversations (self-introduction, personal and environmental questions), read simple sentences, and write Arabic letters correctly according to the rules.